Prentice Hall literature : timeless voices, timeless themes the British tradition - Don Graham, et. Al. (Unites States of America : Prentice-Hall, 2000)
To get the whole of British literature in your mind, you might begin with two funerals. These ceremonies occurs 1,500 years apart, but each honors a persons a great importance.
Unit1. From Legend to History -- Unit2. Celebrating Humanity -- Unit3. A Turbulent Time -- Unit4. Rebels and Dreamers -- Unit5. Progress and Declines -- Unit6. A Time of Rapid Changes .
Includes index.
Keywords: LITERATURE